Laboratory Medicine Impact on Population Health in Arizona: Sonora Quest Implementation of the Kidney Profile. (11th September 2019) - Montgomery, Elizabeth; Ivie, James; Zeigler, Kim; Cohen, Robert; Clark, Jennifer
Abstract: Introduction: Thirty million American adults are estimated to be living with chronic kidney disease (CKD), with over 80% unaware of the condition that puts them at increased risk for cardiovascular events and progression to kidney failure and death. In primary care populations, almost 90% of adults with type 2 diabetes and CKD are not currently diagnosed, and as many as 50% of patients with advanced CKD remain undiagnosed. There is underutilization of urinary albumin-creatinine ratio (uACR) testing in people at risk for CKD. Less than 10% of those with hypertension and less than 40% of those with diabetes are assessed for albuminuria. Sonora Quest Laboratories (SQL) extracted data regarding CKD testing in Arizona. Of 604, 328 people with laboratory evidence of diabetes, 79% were overdue for albuminuria testing. Significant gaps in diagnosis of individuals with laboratory evidence of CKD were identified as well. Methods: The National Kidney Foundation (NKF) and the American Society for Clinical Pathology (ASCP) have implemented a national strategy to promote utilization of the Kidney Profile and improve CKD outcomes. NKF and ASCP are working in concert with SQL and NKF of Arizona to engage Arizona's primary care providers in this effort. The goal is to enhance CKD-related data accuracy in the laboratory information system and to improve CKD recognition, diagnosis, and risk stratification in primary care population health throughout Arizona. Conclusion: Widespread implementation of the Kidney Profile will improve recognition and risk stratification for CKD. This campaign will positively impact primary care utilization of the NKF/ASCP Choosing Wisely recommendation for CKD assessment: do not request just a serum creatinine to test adult patients with diabetes and/or hypertension for CKD; use the Kidney Profile (serum Creatinine with eGFR and urinary albumin-creatinine ratio).